Bureaucracy, the Holocaust and techniques of power at work - Stewart Clegg (Management Revue, 2009)
The generational properties of organization theory are an increasing topic for analysis, usually in terms of what is addressed and how it is addressed. Some writers have alerted us to the importance of those social issues that are not addressed. Combining the idea of generational scholarship with the idea of those non-issues that remain unaddressed, this paper highlights how some of the events of the Second World War, which authorities agree was a generational defining and demarcating experience, have been neglected in organization theory. Nowhere is this more clearly demonstrated than in the Holocaust. Strangely, this practical experiment in organizational design and practice seems to have elided almost all interest by organization theorists, whether functionalist or critical. The paper addresses this elision and draws on the work of Goffman, Foucault and Bauman to address the very material conditions of organizational power and raise some ethical issues about the commitments of organization scholars.
Keywords: 650; power; total institutions; holocaust; Goffman; Foucault; Bauman